2016
DOI: 10.1109/jphotov.2016.2566883
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Sputtered Cu(In,Ga)Se2Absorbers for Photovoltaics: A Review

Abstract: Quaternary sputtering is a promising alternative to more established deposition methods for the fabrication of Cu(In,Ga)Se 2 (CIGS) thin films for photovoltaics (PV). In this technique, a single sputtering target containing all four constituents is employed to deposit the CIGS film. Quaternary sputtering offers several advantages over other deposition methods, including excellent uniformity over large areas, high material usage, and less reliance on toxic Se precursors such as H 2 Se. Despite these advantages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…Instead of employing a postselenization process, we have previously reported that Se deficiency can be overcome by sputtering from a Se‐rich CIGS target or by extra Na doping . However, the cell efficiency of the single‐target sputtering process without postselenization seems to be limited to 10%–11% . Further development is required so that it can compete with other processes.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of employing a postselenization process, we have previously reported that Se deficiency can be overcome by sputtering from a Se‐rich CIGS target or by extra Na doping . However, the cell efficiency of the single‐target sputtering process without postselenization seems to be limited to 10%–11% . Further development is required so that it can compete with other processes.…”
Section: Introductionmentioning
confidence: 99%
“…As expected for samples grown with vacuum methods, not based on a three-stage approach, these samples do not host metal grading. 12…”
Section: Experimental Setup and Samples Preparation Films Growthmentioning
confidence: 99%
“…In the industrial production of Cu(InGa)Se 2 (CIGS) photovoltaic devices, absorbers are usually produced by a two-step process comprising sputter deposition of a Cu-In-Ga alloy precursor, followed by post-selenization and sulfurization [ 1 , 2 ]. Sputtering has great advantages when the technology is transferred from laboratory-scale solar cells to production-scale panels, because it produces large-area film homogeneity [ 3 5 ]. Another promising method is based on the sputtering of CIGS quaternary targets and post-annealing; it involves high materials usage and less reliance on toxic selenium powder or H 2 Se [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various Se-free fabrication routines have been reported [ 8 – 10 ]. For example, Frantz et al [ 5 ] and Chen et al [ 6 ] obtained CIGS device conversion efficiencies of 8%–10% by using one-step sputtering at high substrate temperatures with no post-treatment. However, the efficiency of a solar cell prepared in a Se-free atmosphere is far less than those prepared in a Se-containing annealing atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation